Associations Between Teacher Ratings and Direct Assessment of Elementary Students' Speech and Language Skills. (September 2021) - Chow, Jason C.; Frey, Jennifer R.; Naples, Lauren H.
We investigated the associations between teacher-rated and direct assessments of early elementary students' speech and language skills to explore whether using teachers as primary screeners yielded assessment data that reliably identified young students with language difficulties who many need a more comprehensive evaluation. We assessed first- and second-grade students ( N = 365) on syntax, morphology, and vocabulary, screened for global speech and language development, and analyzed a teacher-completed norm-referenced communication rating scale. Teacher-rated language significantly predicted students' latent language skills, and teachers' ratings of students' communication skills were not influenced by students' gender, race/ethnicity, English language learner status, or special education status. We conclude with a discussion of implications for school-based research, assessment, and practice.